44.2k views
3 votes
Solve it

\sf \: 5(x - 9) + 3(x + 4) = 2(x - 6)


User Coreyward
by
5.4k points

2 Answers

1 vote

Answer:

x=3.5

Explanation:

5(x-9)+3(x+4)=2(x-6)

5x-45+3x+12=2x-12

8x-33=2x-12

8x-2x=-12+33

6x=21

x=21÷6

=3.5

Hope it helps!!!

User Bart Vangeneugden
by
5.8k points
4 votes

Answer:


\huge{x = (7)/(2) }

Explanation:

5(x - 9) + 3(x + 4) = 2(x - 6)

First expand the terms in the bracket

That's

5x - 45 + 3x + 12 = 2x - 12

Simplify

8x - 33 = 2x - 12

8x - 2x = 33 - 12

6x = 21

Divide both sides by 6


(6x)/(6) = (21)/(6) \\ x = (21)/(6)

Simplify

We have the final answer as


x = (7)/(2) \\

Hope this helps you

User CRS
by
5.0k points